Transformation of wood powder carbon template into biomorphic silicon carbide / Husna Elias...[et al.] - Elias, Husna; A., Kalam; Abd Rahman, Noorleha; Koay, Mei Hyie (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Liquid silicon infiltration (LSI) process is a cost effective process to produce biomorphic silicon carbide (SiC) ceramic. In this study, the production of biomorphic silicon carbide from wood powder precursors was investigated. Two types of wood powders were used which were Kapur and Dark Red Meranti. Wood powders were compacted into cylindrical shaped without any adhesive. Biocarbon template was produced via pyrolysis process at 850°C in controlled atmosphere, subsequently infiltrated with melting silicon at 1500°C. Pyrolysis was conducted using double stage process to avoid any cracks. The compacted sample was carbonized with slow heating rate of 1°C/min at temperature 200°C to 500°C. The heating rate was increased to 2°C/min until the pyrolysis process completed. The infiltration process was done by varying the holding time from 2 to 4 hours. The effect of holding time was analyzed by using density and X-ray diffractometer (XRD analysis). The characteristic of the biocarbon template and biomorphic silicon carbide were analyzed by scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS). Due to compaction process, the microstructure of biocarbon produced was found homogenous and uniform with pore size less than 2μm. The pore size and porosity reduced after infiltration process but the density increased. By increasing holding time, the density also increased, which indicates better SiC formation. SEM micrograph shows that the thickness of SiC formation increased by prolonging the holding time. Dark Red Meranti was found to be denser and exhibited better formation of SiC compared to Kapur.